Role of Na+/Ca2+ Exchanger-Mediated Ca2+ Entry in Pressure-Induced Myogenic Constriction in Rat Posterior Cerebral Arteries - Toshihide Kashihara; Koichi Nakayama; Toshio Matsuda; Akemichi Baba; Tomohisa Ishikawa (Elsevier, 2009)
Abstract.: The involvement of Ca2+ entry via the Na+/Ca2+ exchanger (NCX) in myogenic constriction of rat posterior cerebral arteries was investigated. RT-PCR identified mRNA for NCX1, 2, and 3 in the arteries. Na+ removal increased [Ca2+]i, which was reduced by the NCX inhibitor SEA0400. SEA0400 inhibited the development, but not the steady-state, of pressure-induced myogenic constriction, whereas it decreased both the initial and sustained phases of [Ca2+]i elevation. These results suggest that Ca2+ entry via NCX is involved in the development, but not the steady-state, of pressure-induced myogenic constriction. Keywords:: Na+/Ca2+ exchanger (NCX) 1, arteriograph, fura 2